Pesan Dakwah Lingkungan Pada Foto Jurnalistik “Setahun Citarum Harum” - syawal febrian darisman; Ujang Saepullah; Betty Tresnawaty (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2020)
ABSTRACTThe purpose of this study was to determine the meaning of a moral message from a series of photo stories about the Citarum river. The study used a qualitative approach with the Charles Sanders Pierce model of semiotics. Where, Pierce's semiotic model is related to the triangle of meaning, namely the sign, object, and interpretant. The results showed that the moral message contained in this photo story is the importance of protecting the environment, especially rivers. Because rivers can support various living things such as animals, plants, and even humans. Then the photo of this story also shows the facts in the field so that people are aware and able to appreciate the river. Furthermore, this moral message is related to the process of constructive criticism for the government to prioritize resolving the Citarum river problem. The main moral message in the journalistic photo